Immersive Human-Centered Computational Analytics - Stuerzlinger, Wolfgang; Dwyer, Tim; Drucker, Steven; Gorg, Carsten; North, Chris; Scheuermann, Gerik (Immersive Analytics. Lecture Notes in Computer Science, 2018)
In this chapter we seek to elevate the role of the human in human-machine cooperative analysis through a careful consideration of immersive design principles. We consider both strategic immersion through more accessible systems as well as enhanced understanding and control through immersive interfaces that enable rapid workflows. We extend the classic sensemaking loop from visual analytics to incorporate multiple views, scenarios, people, and computational agents. We consider both sides of machine/human collaboration: allowing the human to more fluidly control the machine process; and also allowing the human to understand the results, derive insights and continue the analytic cycle. We also consider system and algorithmic implications of enabling real-time control and feedback in immersive human-centered computational analytics.